A new species of Gomphonema (Bacillariophyta) from Xingkai Lake, China - Ge, Lei; Liu, Yan; Kociolek, Patrick; Fan, Yawen (Phytotaxa, 2014)
During an extensive survey of diatoms from Xingkai Lake, China, one unusual species of the genus Gomphonema was discovered. Detailed morphology of this species is presented using light (LM) and scanning electron microscopy (SEM). These specimens are described as new and named Gomphonema subinsigniforme sp. nov. It is distinguished from other known species of Gomphonema by its shape, being tumid at the centre of valves, with acute headpole, and narrow rounded footpole. Morphological features and ecological parameters of this species are compared to others in the genus.